Stage I synchronous multiple primary non-small cell lung cancer: CT findings and the effect of TNM staging with the 7th and 8th editions on prognosis - Li, Jingxu; Yang, Xinguan; Xia, Tingting; Guan, Yubao; Zhong, Nanshan (Journal of Thoracic Disease; Vol 9, No 12 (December 29, 2017): Journal of Thoracic Disease, 2017)
Background: Studies have reported that up to 8% of non-small cell lung cancers (NSCLC) involve multiple lesions; no detailed study has assessed the prognosis of early synchronous multiple primary non-small cell lung cancer (SMPNSCLC) (T1N0M0, T2aN0M0). We aimed to assess the spiral CT manifestations of SMPNSCLC during stage I and evaluate the effect of TNM staging with the 7th and 8th editions on the prognosis. Methods: We retrospectively analyzed the data of patients who were examined, operated, and pathologically confirmed as having NSCLC from January 1, 2009, to December 31, 2010, and were followed-up for 5 years. The number of cases with stage I SMPNSCLC and solitary primary NSCLC (SPNSCLC) was 36 and 133 as per the 7th edition TNM staging system and 34 and 111 as per the 8th edition TNM staging system, respectively. The relationship between sex, age, smoking history, emphysema, surgical procedure, pathological type, tumor location, and tumor size was evaluated between the two groups, along with the correlation between prognosis and TNM staging with the 7th and 8th editions. Results: A total of 1,948 cases of NSCLC underwent surgery, including 36 cases of stage I SMPNSCLC (77 lesions; 1.85%) with an age of onset of 44–86 years (median age, 60 years). The tumors primarily included adenocarcinoma (93.5%), with a diameter of 0.4–4.5 cm (median, 2.3 cm). CT indicated round/oval tumors in 81.8% cases, lobulation in 79.2% cases, spiculation sign in 70.1% cases, bronchial truncation sign in 31.2% cases, and pleural indentation in 75.3% cases. Moreover, CT indicated the presence of 36 (46.8%) solid nodules and 41 (53.2%) sub-solid nodules. With the 7th edition TNM staging system, the 5-year overall survival (OS) and disease-free survival (DFS) rates for stage ⅠSMPNSCLC were 86.1% and 72.2%, respectively, which did not significantly differ from the prognosis of 133 cases of stage I SPNSCLC (P=0.587, P=0.273). With the 8th edition TNM staging system, the 5-year OS and DFS rates for stage Ⅰ SMPNSCLC were 88.2% and 73.5%, respectively, which also did not significantly differ with the prognosis of 111 cases of stage I SPNSCLC (P=0.413, P=0.235). Conclusions: Adenocarcinoma was the main pathological type among the cases with stage I SMPNSCLC. Multiple synchronous lesions almost had the malignant characteristics of primary lung cancer, particularly the presence of single or multiple sub-solid nodules. Moreover, stage I SMPNSCLC has a similar prognosis as stage I SPNSCLC. The postoperative outcomes of stage I SMPNSCLC patients remained consistent regardless of whether the 7th or 8th edition TNM staging system was used for staging.